GENDER STEREOTYPES IN SPORTS DISCOURSE - Knyazyan, Anna; Haytyan, Lusine (Armenian Folia Anglistika, 2024)
The article is devoted to the study of gender stereotypes in sports discourse. Despite the fact that institutional analysisas already penetrated gender studies, there are very few studies devoted to such a truly ”masculine” activity as professional sports. This determines the relevance of the topic of this work. Sport as a social institution is an ideal opportunity to study male and female stereotypes. Gender stereotypes permeate every aspect of human personality and appearance, and dictate how men and women should act, think and behave. Gender embodies a pattern of relations that evolves over time to define masculinity and femininity, structuring and regulating people’s relation to society. Gender stereotypes are especially clearly visible in professional sports. Professional sports s seen as an activity in which the differences between males and females are manifested, as well as the dominance of the former over the latter. The study was conducted on the material of sports press in the period from 2018–2023.